Antimicrobial resistance: Concerns of healthcare providers and people with CF - Bullington, Wendy; Hempstead, Sarah; Smyth, Alan R; Drevinek, Pavel; Saiman, Lisa; Waters, Valerie J; Bell, Scott C; VanDevanter, Donald R; Flume, Patrick A; Elborn, Stuart; Muhlebach, Marianne S (Journal of cystic fibrosis, 2021)
BACKGROUND: Chronic lung infections and their treatment pose risks for the development of antimicrobial resistance (AMR) in people with cystic fibrosis (PWCF). In this study, we evaluated the attitudes of healthcare providers' (HCP) and PWCF or their parents' toward AMR within the international CF community. METHODS: HCP and PWCF identified through listservs and CF-related organizations were asked to complete an AMR centered survey, with additional questions on antimicrobial stewardship (AMS) for HCP. Descriptive analyses are reported. RESULTS: The responding 443 HCP and 464 PWCF/Parents were from 30 and 25 countries, respectively. Sixty-two percent of HCP and 56% of PWCF stated they were "very concerned" about AMR, with Pseudomonas spp. and Burkholderia spp. considered the most concerning organisms for both HCP and PWCF/Parents. Non-tuberculous mycobacteria were of greater concern to HCP compared to PWCF/Parents. There was a discrepancy regarding AMR education to PWCF, with 80% of HCP stating having discussed this with PWCF/Parents, but only 50% of PWCF recalling such discussions. CONCLUSION: These results highlight that AMR is relevant to CF HCP and PWCF internationally, indicating that educational tools and research are warranted.
Keywords: infekce bakteriemi rodu Burkholderia; Pseudomonas Infections; Health Personnel; Burkholderia Infections; průzkumy a dotazníky; Female; Patients; pacienti; ženské pohlaví; zdravotnický personál; Surveys and Questionnaires; cystická fibróza; lidé; bakteriální léková rezistence; pseudomonádové infekce; Male; Cystic Fibrosis; Health Knowledge, Attitudes, Practice; zdraví - znalosti, postoje, praxe; mužské pohlaví; Drug Resistance, Bacterial; Antimicrobial Stewardship; antibiotická politika; Humans